Behavioristic Counseling Model Based On Audiovisual Media to Increase Solidarity In Junior High School Students - Bau, Bau Ratu; Dhevy Puswiartika; Syahril; Yusdin Gagaramusu; Suhrah; Ninil Elfira (Indonesian Journal of Learning Education and Counseling, 2024)
This article discusses the behavioristic counseling model of role-play collaboration techniques based on audiovisual media to increase the solidarity of state junior high school students in the Sigi district. This study aims to implement the audiovisual media-based behavioral counseling model of role-play collaboration techniques to increase student solidarity. increasing student solidarity is expected to minimize the occurrence of conflicts between students and contribute to creating peaceful schools. This study used the Research and Development (R&D) method. Data collection techniques in this study used interviews and questionnaires. The results of the study show that: (1) the average score of all assessment subjects as much as 93% of guidance and counseling teachers stated that counseling models and guidelines were very easy to implement. (2) based on the recapitulation table of student responses, it shows that the strongly agree category is 93.12%, which indicates a behavioristic counseling model, role play collaboration techniques based on audiovisual media, can increase the solidarity of junior high school students in Sigi Regency